On reflexive edge strength of generalized prism graphs - Muhammad Irfan; Martin Baca; Andrea Semanicova-Fenovcikova (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
Let G be a connected, simple and undirected graph. The assignments 0, 2, …, 2kv to the vertices and 1, 2, …, ke to the edges of graph G are called total k-labelings, where k = maxke, 2kv. The total k-labeling is called an reflexive edge irregular k-labeling of the graph G, if for every two different edges xy and x′y′ of G, one haswt(xy)=fv(x)+fe(xy)+fv(y)≠wt(x′y′) = fv(x′) + fe(x′y′) + fv(y′).The minimum k for which the graph G has an reflexive edge irregular k-labeling is called the reflexive edge strength of G. In this paper we investigate the exact value of reflexive edge strength for generalized prism graphs.